Between Rabin and Arafat A Political Diary Behind the Oslo Deal, 1993-1994 - Neriah, Jacques (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book shares first-hand insights into the implementation of the Oslo Accords between Israel and the Palestinians, written by a high-ranking Israeli military intelligence officer and former foreign policy advisor to Israel's fifth prime minister, Yitzhak Rabin. It offers a diary of the political events surrounding the Israeli prime minister in 1993-1994, focusing on a key turning point in the Israeli-Arab conflict - those crucial days when Rabin had to choose between promoting a peace process with the Palestinians or trying to strike a deal with the Syrians and waiting for the Jordanians to join. The book sheds new light on Rabin's attitudes towards the Palestinians, on his meetings with Yasser Arafat, and on what went on behind the scenes of the official diplomatic negotiations. Readers will learn about the power struggles and ego-driven rivalries between Israeli politicians and high-ranking generals, about the relationship between politicians and the media, and about problems such as the leaking of sensitive information to the press. This book will be of interest not only to scholars, but also and more importantly to policymakers around the world, and to anyone interested in the Israeli-Palestinian conflict and finding a two-state solution in the region. "A vital and extremely well-written book, not only for the academia, but above all for the decision makers across the globe, West and East, North and South, in fact anyone who talks about a two-state solution in the region". Arno Tausch, Professor of Political Science, Innsbruck University, Austria.
Chapter 1. Prime Minister for a second time -- Chapter 2. The Syrian track and the PLO probes -- Chapter 3. The Dilemma between the Palestinian and Syrian tracks -- Chapter 4. Rabin's vision of Russia and its commonwealth states -- Chapter 5. In preparation for the signing with Arafat -- Chapter 6. First work meeting between Rabin and Arafat in Cairo -- Chapter 7. A trip to Cairo with Shimon Peres -- Chapter 8. The talks in Taba, The Rivalries and the Misunderstandings -- Chapter 9. A Crisis in Taba and Talks in Cairo -- Chapter 10. Rabin's visit to the White House -- Chapter 11. Meeting in Paris -- Chapter 12. Meeting Arafat in Tunis -- Chapter 13. Coordination Meetings with the Americans -- Chapter 14. Second meeting with Arafat -- Chapter 15. A decisive meeting between Rabin and Arafat -- Chapter 16. The meeting with the King of Morocco -- Chapter 17. Between Peres and Arafat -- Chapter 18. Wading through the Middle Eastern swamp -- Chapter 19. Meeting with the former Lebanese President Amin Gemayel in Paris -- Chapter 20. Shimon Peres and the Cairo accord with Arafat -- Chapter 21. The massacre in Hebron -- Chapter 22. Negotiations in Washington -- Chapter 23. Meeting the Pope in the Vatican -- Chapter 24. Arafat's deceptions -- Chapter 25. Final days by Rabin's side.
Keywords: Middle East-Politics and government; Peace; World politics; Middle East-History.; Terrorism; Political violence; Middle Eastern Politics; Peace and Conflict Studies; Political History; History of the Middle East; Terrorism and Political Violence